2013
DOI: 10.3892/mmr.2013.1564
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects of the COMT Val158Met genotype on verbal fluency in healthy adults

Abstract: Cognitive performance in healthy individuals is associated with gender differences in specific tests; a female advantage has been demonstrated in language tests, whereas a male advantage has been demonstrated in spatial relation examinations. The prefrontal cortex (PFC) mediates important cognitive domains and is influenced by dopamine (DA) activity. The single nucleotide polymorphism (SNP) rs4680 in the catechol‑O‑methyltransferase (COMT) gene results in an amino acid substitution from valine (Val) to methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The presence of an interaction between COMT val 158 met genotype and sex on face recognition is consistent with other studies that have found sex to affect the impact of the COMT polymorphism on cognitive phenotypes (e.g., O’Hara et al, 2006 ; Barnett et al, 2007 ; Soeiro-De-Souza et al, 2013 ; Gurvich and Rossell, 2015 ). O’Hara et al (2006) reported an interaction between COMT and sex on verbal memory, with male val homozygotes outperforming heterozygote and met homozygote men while females did not differ as a function of genotype.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The presence of an interaction between COMT val 158 met genotype and sex on face recognition is consistent with other studies that have found sex to affect the impact of the COMT polymorphism on cognitive phenotypes (e.g., O’Hara et al, 2006 ; Barnett et al, 2007 ; Soeiro-De-Souza et al, 2013 ; Gurvich and Rossell, 2015 ). O’Hara et al (2006) reported an interaction between COMT and sex on verbal memory, with male val homozygotes outperforming heterozygote and met homozygote men while females did not differ as a function of genotype.…”
Section: Discussionsupporting
confidence: 90%
“…Activity of the COMT enzyme is affected by variation in the gene coding for the COMT, which includes the COMT val 158 met polymorphism ( Chen et al, 2004 ). COMT activity is also regulated by oestrogen (e.g., Jiang et al, 2003 ), and certain effects of the COMT polymorphism on cognition appear to be sex-specific (e.g., Barnett et al, 2007 ; Soeiro-De-Souza et al, 2013 ; Gurvich and Rossell, 2015 ). This study investigated the potential sex-specific effects of the COMT val 158 met polymorphism on memory for faces in young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although there are well-documented sex differences in DA transmission (Becker, 1990) and exploration of sex differences in public health research has been an NIH priority since the 1990s (Mazure and Jones, 2015), only a limited number of studies have tested for sex differences in associations between DA SNPs and behavior. Most of these studies had small sample sizes and conflicting results (Holtzer et al, 2010; Soeiro-De-Souza et al, 2013). The larger sample size here allows for a more conclusive investigation of whether males and females differ in how DA genotype may influence their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, low voltage α has been associated with low activity levels in COMT, a catechol- O -methyltransferase that catalyzes the O -methylation of neurotransmitters like dopamine, epinephrine, and norepinephrine ( Enoch et al, 2003 ). COMT has been regularly associated with language performance and processing, and language acquisition, particularly with verbal fluency ( Krug et al, 2009 ; Soeiro-De-Souza et al, 2013 ; Sugiura et al, 2017 ), but also with reading abilities ( Landi et al, 2013 ). Finally, ZNF804A, a zinc finger binding protein, modulates hippocampal γ oscillations and thus the coordination of hippocampal and prefrontal distributed networks ( Cousijn et al, 2015 ).…”
Section: Searching For Language Oscillogenome Candidatesmentioning
confidence: 99%